2006
DOI: 10.1159/000093408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Tirofiban Administration on Myocardial Salvage in Patients with Acute Myocardial Infarction Undergoing Infarct-Related Artery Stenting

Abstract: Background/Aims: The timing of GpIIb/IIIa inhibitor administration may be important in achieving early epicardial and myocardial reperfusion. We evaluated the effect of early tirofiban on myocardial salvage and cardiovascular outcome in patients with acute myocardial infarction (AMI) undergoing infarct-related artery stenting. Methods: Patients (n = 66) with a first AMI presenting <6 h from onset of symptoms were randomized to either early administration of tirofiban in the emergency room (n = 32) or later adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
(32 reference statements)
2
22
0
Order By: Relevance
“…Previous studies have shown that the application of platelet glycoprotein IIb/IIIa receptor antagonists before primary PCI obviously improves the prognosis of patients (Cutlip et al, 2003;Lee et al, 2003;Zeymer et al, 2005;Emre et al, 2006;Gabriel et al, 2006;Gibson et al, 2006;Rakowski et al, 2007;De Luca et al, 2008). This finding is consistent with the results of our research.…”
Section: Disscussionsupporting
confidence: 93%
“…Previous studies have shown that the application of platelet glycoprotein IIb/IIIa receptor antagonists before primary PCI obviously improves the prognosis of patients (Cutlip et al, 2003;Lee et al, 2003;Zeymer et al, 2005;Emre et al, 2006;Gabriel et al, 2006;Gibson et al, 2006;Rakowski et al, 2007;De Luca et al, 2008). This finding is consistent with the results of our research.…”
Section: Disscussionsupporting
confidence: 93%
“…This result was supported by many studies which consistently reported better outcomes with upstream or early use of glycoprotein IIb/IIIa inhibitor compared with deferred treatment or other strategies (LOE 1 [452][453][454][455][456][457][458][459][460][461][462][463][464][465][466][467] ; LOE 2 468 -473 ; LOE 3 474 ; LOE 4 [475][476][477][478] ; LOE 5 479 ).…”
Section: Consensus On Sciencementioning
confidence: 74%
“…These baseline characteristics were also statistically non-significant in the studies done by Tuba et al (2006) 25 who compared the high bolus dose regimen with the standard regimen. Also, these factors were statistically non-significant in the study done by Emre et al (2006) 26 who evaluated the effect of early tirofiban on myocardial salvage and cardiovascular outcome in patients with acute myocardial infarction (AMI) undergoing infarct-related artery stenting. As the success rate is inversely correlated to the duration of symptoms, also is inversely correlated to the time to treatment, 27 so, in this study the door to needle time and door to balloon time were tried to be nearly in the same range in all groups (door to needle time was around 30 min and door to balloon time was around 90 min in all study groups) in order not to affect the angiographic results.…”
Section: Discussionmentioning
confidence: 99%